Scribble modulates the MAPK/Fra1 pathway to disrupt luminal and ductal integrity and suppress tumour formation in the mammary gland. - Nathan J Godde; Julie M Sheridan; Lorey K Smith; Helen B Pearson; Kara L Britt; Ryan C Galea; Laura L Yates; Jane E Visvader; Patrick O Humbert (PLoS Genetics, 2014)
Polarity coordinates cell movement, differentiation, proliferation and apoptosis to build and maintain complex epithelial tissues such as the mammary gland. Loss of polarity and the deregulation of these processes are critical events in malignant progression but precisely how and at which stage polarity loss impacts on mammary development and tumourigenesis is unclear. Scrib is a core polarity regulator and tumour suppressor gene however to date our understanding of Scrib function in the mammary gland has been limited to cell culture and transplantation studies of cell lines. Utilizing a conditional mouse model of Scrib loss we report for the first time that Scrib is essential for mammary duct morphogenesis, mammary progenitor cell fate and maintenance, and we demonstrate a critical and specific role for Scribble in the control of the early steps of breast cancer progression. In particular, Scrib-deficiency significantly induced Fra1 expression and basal progenitor clonogenicity, which resulted in fully penetrant ductal hyperplasia characterized by high cell turnover, MAPK hyperactivity, frank polarity loss with mixing of apical and basolateral membrane constituents and expansion of atypical luminal cells. We also show for the first time a role for Scribble in mammalian spindle orientation with the onset of mammary hyperplasia being associated with aberrant luminal cell spindle orientation and a failure to apoptose during the final stage of duct tubulogenesis. Restoring MAPK/Fra1 to baseline levels prevented Scrib-hyperplasia, whereas persistent Scrib deficiency induced alveolar hyperplasia and increased the incidence, onset and grade of mammary tumours. These findings, based on a definitive genetic mouse model provide fundamental insights into mammary duct maturation and homeostasis and reveal that Scrib loss activates a MAPK/Fra1 pathway that alters mammary progenitor activity to drive premalignancy and accelerate tumour progression.